Diagnosis and Management of an Isolated Pediatric Plexiform Neurofibroma Involving the Hepatic and Celiac Plexus Using Multimodality Approach: Problem Solving with Diffusion-Weighted Magnetic Resonance Imaging - Merel M. Scheurkogel; June Koshy; Kenneth J. Cohen; Thierry A. G. M. Huisman; Thangamadhan Bosemani (Georg Thieme Verlag KG, 2013)
Abstract Plexiform neurofibroma with involvement of the gastrointestinal tract is a very rare entity in children. Here, we present a rather unique case of a 9-year-old boy with no clinical signs or features of neurofibromatosis type 1. A periportal mass lesion was incidentally found after performing an ultrasound in this previously healthy child. Computed tomographic scan was subsequently performed which showed a low-density mass in a periportal distribution with extension along the celiac axis. Because the findings were nonspecific, a pre- and postcontrast magnetic resonance imaging of the abdomen was performed which included diffusion-weighted imaging. The lesion was then confirmed to be a plexiform neurofibroma with open biopsy. Management of plexiform neurofibromas varies widely. Given the extensive nature of the lesion, managing the patient with follow-up rather than surgical excision was favored.